Materinstvo onkraj sanj - Drglin, Zalka (Zdravstveno varstvo, 2003)
It is estimated that in Slovenia out of nearly 18.000 births, 14.000 women suffer from postpartum depression; 1.800 to 3.600 from postpartum depression -one quarter of these for serious depression and around 36 women from postpartum psychosis. Women suffer more than it is usually imagined and their suffering should be given more attention. Women with mood disorders associatedwith childbearing should be given more help on the regular basis. A network of social and health services which would offer various choices shouldbe established. Assertiveness, team work and continuity of care for childbearing women should become a part of an effective modern public mental health system in Slovenia. Furthermore, established concepts of maternity needto be given a critical consideration.
Keywords: duševno zdravje; materinstvo; mental health; poporodno obdobje